Health-related quality of life in patients with Achilles tendinopathy: Comparison to the general population of the United Kingdom. Issue 7 (October 2022) - Lewis, T.L.; Yip, G.C.K.; Robertson, K.; Groom, W.D.; Francis, R.; Singh, S.; Walker, R.; Abbasian, A.; Latif, A.
Abstract: Background: There is little evidence available regarding the impact of Achilles Tendinopathy (AT) on health-related quality of life (HRQOL). The primary aim of this study was to quantify the clinical and health-related quality-of-life patient-reported outcome measures for a population presenting with either mid-substance or insertional Achilles tendinopathy. Methods: A prospective comparative observational study of consecutive patients with AT presenting for extracorporeal shockwave therapy (ESWT) at a large teaching hospital. The primary outcome was assessment of a validated health-related quality of life PROMs (Euroqol EQ-5D-5L) and comparison to 2 general UK population datasets. The secondary outcomes were Visual Analogue Pain Scale (VAS-Pain) and two validated foot-specific patient reported outcome measures (Foot Function Index (FFI) and Victorian Institute of Sports Assessment-Achilles (VISA-A)). Results: Between March 2014 and June 2021, 320 consecutive patients (125 male; 195 female) were diagnosed with AT and referred for a first course of ESWT. EQ-5D-5L PROMs were prospectively collected for 303 of these patients (94.7%). The mean age (± standard deviation(SD)) was 52.1 ± 11.4 years. The mean EQ-5D-5L Index score (mean±SD) for the AT cohort was 0.783 ± 0.131. Patients less than 55 years with AT had a statistically significantly worse quality of life compared with members of the same age group in the general population. The mean VAS-Pain, FFI, VISA-A clinical outcome scores were 6.0 ± 2.3, 49.5 ± 21.2 and 34.1 ± 14.4 respectively. There was a statistically significant moderate correlation between HRQOL and clinical PROMs (VAS-Pain and FFI vs EQ-5D) however there was no correlation with age. Conclusion: This study demonstrates that patients under the age of 55 with AT have a significantly reduced quality of life compared with the general population. Level of evidence: III